Recent Advances on Organic Fluorescent Probes for Stimulated Emission Depletion (STED) Microscopy - Xu, Ruohan; Xu, Yanzi; Wang, Zhi; Zhou, Yu; Dang, Dongfeng; Meng, Lingjie (Combinatorial Chemistry & High Throughput Screening, 2021)
Stimulated emission depletion (STED) microscopy has become a useful tool for visualization and dynamic monitoring at an ultra-high resolution in biological research and material science. For STED technology, fluorescent probes are irreplaceable in the imaging process. Among these probes, organic fluorescent probes have superior photo-stability, high brightness, large Stokes’ shifts and excellent biocompatibility, thus are widely applied in STED microscopy. Based on this consideration, this review presents the recent advances on organic fluorescent probes for STED microscopy, including typical organic fluorescent probes, aggregation-induced emission luminogens (AIEgens), polymer dots, and other nanoparticles. The applications of organic fluorescent probes in biological imaging, such as in live-cell, live-tissue, and in vivo imaging, as well as in material monitoring at the nanoscale using STED microscopy, are also included. This review provides the guidelines for the design of new materials that can be used to enhance the imaging performance of STED microscopy, thus leading to real-world applications.
Keywords: biological imaging